PROMOTING NATIONALISM IN TEACHING ENGLISH TO PRIMARY SCHOOL STUDENT - Rosi Anjarwati (Universitas Pesantren Tinggi Darul Ulum Jombang, 2015)
Primary School in Indonesia is considered to be a basic formal education which has some specific objectives. It is believed that nationalism should be introduced in these ages to build a person with good nationalism character. Anxiety about young generation’s national character causes consideration of removing English subject from Primary school curriculum while today’s demand of English competency is very high. Many people worry about the influence of western culture that can omit students’ national character if it is taught from Primary School level. In fact, the importance of teaching English at early age is clearly needed to create qualified Indonesian human resources in the future. This article aims to propose idea which can give solution to maintain nationalism through teaching English at primary school by giving some alternative models of teaching method and suggested materials. Key words: Nationalism, Primary School, teaching English Sekolah Dasar di Indonesia adalah pendidikan dasar formal yang memiliki beberapa tujuan tertentu. Banyak pendapat meyakini bahwa nasionalisme seharusnya diperkenalkan pada masa masa ini untuk membentuk insan berkarakter nasional yang baik. Kekhawatiran terhadap karakter nasional generasi muda menjadi pertimbangan dihapusnya mata pelajaran Bahasa Inggris di kurikulum Sekolah Dasar, disisi lain kebutuhan untuk memiliki kompetensi berbahasa Inggris sangatlah tinggi. Banyak orang khawatir terhadap pengaruh budaya barat yang dapat mengilangkan karakter nasional siswa jika Bahasa Inggris diajarkan mulai tingkat Sekolah Dasar. Kenyataanya, pentingnya pengajaran Bahasa Inggris sejak dini sangat diperlukan untuk menciptakan sumber daya manusia yang berkualitas di masa yang akan datang. Artikel ini bertujuan untuk mencetuskan ide yang dapat menjadi solusi mempertahankan nilai nilai nasionalisme melalui pengajaran Bahasa Inggris di Sekolah Dasar dengan memberi beberapa contoh metode pembelajaranalternatif beserta materinya. Kata Kunci: Nasionalisme, Sekolah Dasar, pengajaran Bahasa Inggris